Evaluación del potencial del uso de las algas de arribazón conocidas como Sargazo (Sargassum spp.) (2020)
This project describes the characteristics, properties and potential uses of sargasso seaweed (Sargassum spp.), with an emphasis on its polysaccharides such as fucoidans, alginates and laminarans. Based on a bibliographic compilation of different studies carried out with these algae, a synthesis of the main uses and the most common extraction methods for each polysaccharide is presented. Other less common polysaccharides used in the industry are also included. Finally, a summary of the potential industries where these polysaccharides could be applied according to their characteristics and function, is presented.